2018
DOI: 10.1584/jpestics.d17-052
|View full text |Cite
|
Sign up to set email alerts
|

Viral infection induces different detoxification enzyme activities in insecticide-resistant and -susceptible brown planthopper <i>Nilaparvata lugens</i> strains

Abstract: This study aimed to describe the relationship between viral infection in Nilaparvata lugens (Stål), the brown planthopper (BPH), and different insecticide susceptibilities. BPH-resistant strains were selected using fenthion (an organophosphate) or etofenprox (a pyrethroid); a susceptible strain was used as the baseline colony before insecticide selection. All strains were infected with rice ragged stunt virus (RRSV) or rice grassy stunt virus (RGSV), after which the activities of three detoxification enzymes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Zhou et al [ 40 ] showed that the chronic presence of RSV in L. striatellus could suppress the expression of antiviral genes, TLR13, and promoting virus transmission. There also exists a complex interplay between RRSV and BPH [ 34 , 37 ]. In this study, we demonstrated whether the effect of RRSV on the immunity of BPH could produce any supplement impact on the efficacy of M. anisopliae YTTR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al [ 40 ] showed that the chronic presence of RSV in L. striatellus could suppress the expression of antiviral genes, TLR13, and promoting virus transmission. There also exists a complex interplay between RRSV and BPH [ 34 , 37 ]. In this study, we demonstrated whether the effect of RRSV on the immunity of BPH could produce any supplement impact on the efficacy of M. anisopliae YTTR.…”
Section: Discussionmentioning
confidence: 99%
“…Plant viruses, like other foreign pathogens in the insect system, can trigger the immune response of their host insect vector [ 13 , 32 ]. Yoshikawa et al [ 34 ] reported that both BPH-transmitted viruses (RRSV and RGSV) caused changes in the activity of detoxification enzymes, but at different degrees for different viruses, sexes, and resistant strains. Plant viruses can persist in vector insects, and they co-evolve in more intricate interactions with vector insects [ 33 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, viruses are also known to hamper pest management strategies. For example, it is known that viruses can influence insecticide resistance (Yoshikawa et al, 2018). Furthermore, when viruses infect larvae of pests, they could potentially prevent parasitoids to parasitize them (Robertson et al, 2013).…”
Section: Viral Functions In Biological Control Of Pest Insectsmentioning
confidence: 99%
“…This implies that GSTs can protect insect cells against ROS-induced cell death [ 145 ]. Among etofenprox-selected individuals of Nilaparvata lugens with rice ragged stunt virus (RRSV) infection [ 152 ], activities of GSTs usually increased when the infection rate of RRSV was low [ 153 ]. This suggests that GSTs are important in producing an environment beneficial for viral defense.…”
Section: The Effect Of Gst In Mosquito Cellsmentioning
confidence: 99%